The Influence of Digital Marketing, Business Capital, and HR Competence on the Success of Fashion UMKM Businesses in the Medan Area District - Jefry Holy; Dedy Lazuardi; Widalicin Januarty; Sri Rezeki; Brilian Moktar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effects of digital marketing, business capital, and human resource competencies on the business success of fashion MSMEs in Medan Area District. The research employs a quantitative approach using a survey method with 124 MSME actors as respondents. Data were collected through questionnaires and analyzed using multiple regression analysis to test the hypotheses. The findings reveal that digital marketing, business capital, and human resource competencies each significantly influence business success both individually and simultaneously. Specifically, digital marketing has the highest contribution to business success, followed by human resource competencies and business capital. The study also finds that these three variables collectively explain a substantial proportion of the variance in business success. This research contributes to the existing literature by emphasizing the importance of integrating digital strategies, adequate capital management, and competent human resources in achieving sustainable business performance. Furthermore, the findings provide practical insights for MSME actors to enhance their competitiveness through optimizing digital marketing, improving financial management, and developing human resource capabilities, while future studies are encouraged to explore additional factors such as innovation and market orientation.